Pequena propriedade e cooperativismo no Oeste do Paraná: um estudo à partir da Cooperativa Agroindustrial Lar - Marschall, Clédio Roberto (2005)
The realization of the study objectified to examine the existing relationship between a strategy of the small landowner strengthening and his associative behavior in the universe of the agricultural corporatism Was defined as hypothesis that that strategy would be materialized in the necessity of defending economic interest valorizing of the product and of construction of the small landowner s identity The results of the case study demonstrated that the social-catholicism supplied the bases for the development of the cooperation relationships of the area of inclusion of Cooperativa Agroindustrial Lar in the far west of Paraná especially when of the need of part colonization of that area as well as to do front to the phenomenon of the agricultural mechanization in the beginning of the 1960 s decade In a general way and not limiting the temporality the realization of the search together with the small rural producers and the complementation of study with secondary information lead to the accepting of the formulated hypothesis About the need of economic interest defenses verified the emphasis given by the small owner to aspects such as technical attendance and safety as strategies of improvement of its economic conditions being constituted in the main motivations for the association in the cooperative The hypothesis of production valorizing confirmed the opinion of the associated the recognized in majority the valor given by the cooperative to the small production Besides that they affirmed that the organization has been assisting to the interests of the small property and they see in the diversification of activities and in the agroindustrialization the foundation for its growth The identity element confirmed as well like hypothesis once it was observed in the associates opinion the importance to the colleagueship liaisons friendship and feeling of belonging to one group with the same values and cultural elements referring to the sociable atmosphere found in the cooperative The organization of small producers in turn of the cooperative could be seen still as instruments of regional development for the interoperations established in the system of social organization by activity committees and in the valorizing of diversity of the agricultural activities represent a component of construction of nets of complementarily favoring the creation distribution and multiplication of the economic surpluses in the municipal districts in that makes himself present marking the profile of the regional development